Thermal comfort assessment-a study toward workers' satisfaction in a low energy office building - Shaharon, Mohd Nafiz; Jalaludin, Juliana (Science Publications, 2012)
Problem statement: The government of Malaysia has raised their concerns towards the issue of workers comfort and workspace quality in a Low Energy Office (LEO) building. New energy efficient building concepts and technologies require a revision of comfort standards, to create a suitable thermal condition in avoiding occupant dissatisfaction, adverse effect on their roductivity and overall building performance. Approach: Assessment was conducted using Babuc-A (Portable air quality monitor) and sets of questionnaire adapted from ASHRAE-2004 were 99 respondents selected using a stratified random sampling. Results: This study shows that the thermal comfort zone temperature was identified to be within the range of 21.6-23.6°C and relative humidity of 42-54%. Conclusion: The results suggested that the thermal condition was in the acceptable range of ISO7730 and a lower room temperature was preferred by Malaysian in an office environment compared with the temperature criteria cited in ASHRAE-55. To create an optimum comfortable workplace, temperature between 20-26°C and relative humidity between 40-60% must be maintained. Adequate ventilation must be provided at the minimum rate of 10 l/s of fresh air per person for general office space or every 10 m 2 of floor space.